I'll show a step-by-step. I'm not in the mood to explain right now lol.
2(x-2.6)+2.91=7.71
2x-5.2+2.91=7.71
+5.20 +5.20
2x+2.91=12.91
-2.91 -2.91
2x=10
/2 /2
x=5
---
hope it helps
sorry if it doesn't
Answer:
99 24/25
Step-by-step explanation:
8.33*√144=
8.33*12=99 24/25 or 100 with 8.33 bar
(3)×(-2)=-6 that's the answer
Answer:
the factored equation is ((x^3) + 3x^2) + 2x = 0
Step-by-step explanation:
*The ^ means to the power of.
so you should start off by splitting it into ways, like isolate 2x and start with x^3 and 3x^2, if thats the wrong answer u are not looking for then the other formula is x^3 + 3x^2 + 2x = x • (x^2 + 3x + 2), again just splitting it into ways. since we know the equation is = to 0, we put 2 of them together, and since you can divide everything by x and just put x outside to keep it the same, it would become x^3 + 3x^2 + 2x = x • (x^2 + 3x + 2).
Your Welcome
Answer:
Graph A
Step-by-step explanation: